Histone H1 defect in escort cells triggers germline tumor in Drosophila ovary. - Yang, Z.; Sun, J.; Hu, Y.; Wang, F.; Wang, X.; Qiao, H.H.; Xu, J.; Mao, D.; Ren, X.; Pan, L.X.; Xu, R.G.; Xu, B.W.; et al. (Developmental Biology, 2017)
Drosophila ovary is recognized as one of the best model systems to study stem cell biology in vivo. We had previously identified an autonomous role of the histone H1 in germline stem cell (GSC) maintenance. Here, we found that histone H1 depletion in escort cells (ECs) resulted in an increase of spectrosome-containing cells (SCCs), an ovary tumor-like phenotype. Further analysis showed that the Dpp pathway is excessively activated in these SCC cells, while the expression of bam is attenuated. In the H1-depleted ECs, both transposon activity and DNA damage had increased dramatically, followed by EC apoptosis, which is consistent with the role of H1 in other somatic cells. Surprisingly, H1-depleted ECs acquired cap cell characteristics including dpp expression, and the resulting abnormal Dpp level inhibits SCC further differentiation. Most interestingly, double knockdown of H1 and dpp in ECs can reduce the number of SCCs to the normal level, indicating that the additional Dpp secreted by ECs contributes to the germline tumor. Taken together, our findings indicate that histone H1 is an important epigenetic factor in controlling EC characteristics and a key suppressor of germline tumor.